Analisis Faktor-Faktor yang Mempengaruhi Pilihan Jenis Minuman pada Situasi Konsumsi Hang-Out dan Celebration - Alamsyah, Zeffry; Sumarwan, Ujang; Hartoyo, Hartoyo; Yusuf, Eva Z. (Jurnal Manajemen dan Organisasi, 2010)
Soft-drink market in Indonesia continuously grows in the last ten years; however the growth is varied among soft-drink categories in different years. This encourages practitioners in soft-drink industry to understand what factors influencing the consumer when they buy soft-drink to consume, as this will be beneficial to formulate an effective marketing strategy. This research elaborates factors that are predicted as influencer for consumer in choosing soft-drink to buy and consume during hang-out and celebration situation. From 26 factors of product attributes, consumer characteristics, social, and environmental, there are 11 factors which significantly influence respondent decision to choose any type of soft-drink. These are: age, education, household expenditure, hang-out frequency, product availability, taste, aroma, product freshness, manufacturer reputation, and peer’s choice of drink.  Bottled water, carbonated soft-drink, and ready to drink tea are the most chosen soft-drink categories by respondent.